Change in levels of physical activity after diagnosis of type 2 diabetes: an observational analysis from the NAVIGATOR study. Issue 12 (19th June 2014) - Preiss, D.; Haffner, S. M.; Thomas, L. E.; Sun, J.‐L.; Sattar, N.; Yates, T.; J Davies, M.; McMurray, J. J.; Holman, R. R.; Califf, R. M.; Kraus, W. E.
<x xml:space="preserve">Abstract</x> Increased physical activity is known to be beneficial in people with type 2 diabetes mellitus (T2DM), but it is not known whether individuals change their activity levels after T2DM diagnosis. The present Nateglinide and Valsartan in Impaired Glucose Tolerance Outcomes Research (NAVIGATOR) trial, conducted in participants with impaired glucose tolerance at high cardiovascular risk, assessed ambulatory activity annually using research‐grade pedometers. Oral glucose tolerance tests were performed annually and repeated to confirm T2DM diagnosis. This observational analysis used general linear models to compare step counts before and after T2DM diagnosis in the 2816 participants with the requisite data. Participants were relatively inactive at baseline, taking a median (interquartile range) of 5488 (3258–8361) steps/day, which decreased after T2DM diagnosis by a mean (s.e.) of 258 (64) steps/day (p < 0.0001); however, after adjusting for background trend for activity, step count after T2DM diagnosis was unchanged [mean (s.e.) of 103 (87) fewer steps/day; p = 0.23]. Awareness of T2DM diagnosis had no impact on the trajectory of activity established before the diagnosis.